2020
DOI: 10.1302/2046-3758.96.bjr-2019-0196.r1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a novel double rip-stop technique with medial row knots for rotator cuff repair

Abstract: Aims Many biomechanical studies have shown that the weakest biomechanical point of a rotator cuff repair is the suture-tendon interface at the medial row. We developed a novel double rip-stop (DRS) technique to enhance the strength at the medial row for rotator cuff repair. The objective of this study was to evaluate the biomechanical properties of the DRS technique with the conventional suture-bridge (SB) technique and to evaluate the biomechanical performance of the DRS technique with medial row knots. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In immediate evaluations, we demonstrated that the Plug-Pat can provide a significantly larger refreshed contact area between the graft and bone at time zero, which may optimize the healing biology at the repaired graft-bone interface. 23,24,36,37,56 In the green fluorescent protein–bone marrow chimeric rat model, Nakagawa et al 31 reported that the footprint preparation by drilling small bone holes resulted in more bone marrow–derived cells infiltrating the healing interface when compared with the footprint spongialization by exposing the cancellous bone. Similarly, this special tunnel-based “footprint preparation” using bone tunnel with a larger refreshed bone bed contact area in the Plug-Pat may lead to an increased local outflow of stem cells and other cytokines from the bone marrow for better introduction to the healing interface, thus enhancing graft-to-bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In immediate evaluations, we demonstrated that the Plug-Pat can provide a significantly larger refreshed contact area between the graft and bone at time zero, which may optimize the healing biology at the repaired graft-bone interface. 23,24,36,37,56 In the green fluorescent protein–bone marrow chimeric rat model, Nakagawa et al 31 reported that the footprint preparation by drilling small bone holes resulted in more bone marrow–derived cells infiltrating the healing interface when compared with the footprint spongialization by exposing the cancellous bone. Similarly, this special tunnel-based “footprint preparation” using bone tunnel with a larger refreshed bone bed contact area in the Plug-Pat may lead to an increased local outflow of stem cells and other cytokines from the bone marrow for better introduction to the healing interface, thus enhancing graft-to-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…After biomechanical testing, the width and length of the footprint in the Rect-Pat group, as well as the diameter and depth of the 2 newly fabricated tunnels in the Plug-Pat group, were measured using a vernier caliper (see Appendix Figure A3, available online). 1,56 These parameters were used to calculate the intraoperative refreshing bone bed areas (refreshed contact area between the graft and bone bed) after footprint preparation, which is critical for the graft-bone integration in 2 groups. 31…”
Section: Methodsmentioning
confidence: 99%